2021
DOI: 10.1021/acsbiomaterials.0c01527
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Based Scaffolds in Tissue Engineering

Abstract: A wide range of platforms has been developed for 3D culture of cells in vitro to aggregate and align cells to resemble in vivo conditions in order to enhance communication between cells and promote differentiation. The cellulose skeleton of plant tissue can serve as an attainable scaffold for mammalian cells after decellularization, which is advantageous when compared to synthetic polymers or animal-derived scaffolds. Adjustable variables to modify the physical and biochemical properties of the resulting scaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 54 publications
0
39
0
Order By: Relevance
“…It has been suggested that plant-based biomaterials do not provide sufficient reproducibility, as the plants used were not grown in a controlled environment [109] where soil nutrients and age of the plant can affect structural and mechanical properties in the native leaf structures [110]. While this is a very thoughtful point, it would not be possible to make perfectly reproducible vegetal structures, as genetic and environmental factors similarly influence these properties [111].…”
Section: Additional Considerations For Decellularized Plant-based Biomaterialsmentioning
confidence: 99%
“…It has been suggested that plant-based biomaterials do not provide sufficient reproducibility, as the plants used were not grown in a controlled environment [109] where soil nutrients and age of the plant can affect structural and mechanical properties in the native leaf structures [110]. While this is a very thoughtful point, it would not be possible to make perfectly reproducible vegetal structures, as genetic and environmental factors similarly influence these properties [111].…”
Section: Additional Considerations For Decellularized Plant-based Biomaterialsmentioning
confidence: 99%
“…Therefore, combining in one single material proper 3D-structure, suitable mechanical resistance, and bio-functional groups that can steadily and actively sustain the cell attachment still holds a great challenge. Recently, decellularization of animal and plant tissues has been proposed as a great solution to this issue, but several physical, chemical or enzymatic treatments are necessary preliminary steps to achieve an appropriated scaffold for cell growth and attachment 41 , 42 .…”
Section: Introductionmentioning
confidence: 99%
“…Plant-derived scaffolds have demonstrated their efficiency for tissue engineering applications (Bilirgen et al, 2021;Cheng et al, 2020;Contessi Negrini et al, 2020;Dikici et al, 2019;Fontana et al, 2017;Gershlak et al, 2017;Harris et al, 2021;Hickey et al, 2018;Holmes et al, 2022;Lee et al, 2019;Modulevsky et al, 2016Modulevsky et al, , 2014Robbins et al, 2020;S. H et al, 2021;Toker et al, 2020;Wang et al, 2020;Zhu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%